2015
DOI: 10.1155/2015/901656
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Potential Plant Growth Promoting Rhizobacteria Isolated from Maize (Zea maysL.) in Central and Northern Benin (West Africa)

Abstract: Our study aims to characterize Plant Growth Promoting Rhizobacteria (PGPR) isolated from maize roots in five agroecological zones of central and northern Benin. Sixty samples were collected at the rate of four samples per village and three villages per agroecological zone. Rhizobacteria strains were isolated from these samples and biochemically characterized. These strains were analyzed for some of their PGPR traits like ammonia production and hydrogen cyanide following conventional methods. Microbiological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 19 publications
2
31
2
1
Order By: Relevance
“…According to Laslo, György, Mara, Tamás, Ábrahám and Lányi[21], 63.8% of bacteria isolates from different rhizosphere of monocotyledonous plants solubilized phosphate as against 27.91% from this study.It was observed that none of the isolates from fields growing chickpea from West of Allahabad Agricultural Institute, India produced HCN[42] while in this study 4.65% produced HCN. This result is not comparable to a report by Agbodjato, Noumavo, Baba-Moussa, Salami, Sina, Sèzan, Bankolé, Adjanohoun and Baba-Moussa[43] which revealed that 100% of isolates from maize rhizosphere produced HCN.Isolates B. cereus, B. amyloliquefaciens, B. thuringiensis, Bacillus sp. from this study were able to antagonise the growth of F. graminaerum, which is an agricultural challenge to barley, wheat and maize in South Africa [48, 49].…”
contrasting
confidence: 91%
See 1 more Smart Citation
“…According to Laslo, György, Mara, Tamás, Ábrahám and Lányi[21], 63.8% of bacteria isolates from different rhizosphere of monocotyledonous plants solubilized phosphate as against 27.91% from this study.It was observed that none of the isolates from fields growing chickpea from West of Allahabad Agricultural Institute, India produced HCN[42] while in this study 4.65% produced HCN. This result is not comparable to a report by Agbodjato, Noumavo, Baba-Moussa, Salami, Sina, Sèzan, Bankolé, Adjanohoun and Baba-Moussa[43] which revealed that 100% of isolates from maize rhizosphere produced HCN.Isolates B. cereus, B. amyloliquefaciens, B. thuringiensis, Bacillus sp. from this study were able to antagonise the growth of F. graminaerum, which is an agricultural challenge to barley, wheat and maize in South Africa [48, 49].…”
contrasting
confidence: 91%
“…Seventy eight percent (78%) of the isolates from different monocotyledonic plants' rhizosphere and soil [21], 77.1 % of isolates from chickpea rhizosphere [42], 85.57% of isolates from maize rhizosphere [43] produced ammonia as against 100% ammonia production from this study. This could be as a result of the high nitogen-fixing capacity of both the nitrogen fixers and free living non-symbionts in the rhizosphere of bambara groundnut.…”
Section: Discussionmentioning
confidence: 89%
“…These are: Bacillus panthothenicus; Pseudomonas Cichorii; Pseudomonas Putida; Pseudomonas syringae and Serratia marcescens. They were isolated and characterized from the rhizosphere of maize from different agro-ecological zones of central and northern Benin by [23] and stored at −20˚C in Muller Hinton broth with glycerol (10%) At the laboratory of Biology and molecular typing in microbiology of the University of Abomey-Calavi.…”
Section: Methodsmentioning
confidence: 99%
“…Strains of PGPR: Nine (9) strains of PGPR namely Bacillus polymyxa, Bacillus anthracis, Bacillus thuringiensis, Bacillus circulans, Bacillus panthothenicus, Pseudomonas cichorii, Pseudomonas putida, Pseudomonas syringae and Serratia marcescens were used. These strains were isolated and characterized from the rhizosphere of maize from the different agroecological zones of central and northern Benin by [22] and stored at −20.3˚C in Muller Hinton broth with glycerol (10%) in the laboratory of Biology and molecular typing in microbiology from the University of Abomey-Calavi.…”
Section: Methodsmentioning
confidence: 99%